Male Greeting Practices in Iraqi Culture: Workplace Etiquette and Generational Variation from a Linguistic Perspective (The International Journal of Educational Sciences and Arts, 2026)
This research paper is from a sociolinguistics point of view on male greeting behavior in Iraqi culture focusing mainly on greeting in the workplace and the differences in the different generations. This research aims to examine the interplay of traditional Islamic greeting categories (e.g., “As-salamu alaykum”) within the current sociocultural context of the workplace – given the norms and expectations of the current generation, as well as the humanities of globalization and priming – with reference to politeness theory, face-saving strategies and intercultural communication. The findings demonstrate that there are significant differences in regard to greeting formality, code switching and traditional verbal and nonverbal greetings between older and younger Iraqi men. There are recognizable hierarchies of greetings in the workplace linked to each social status, age, and between professional relationships. The linguistic landscape is a complex one, with urban-rural differences in all regions and the influence of western languages, as well as digital communication. It uses qualitative and quantitative approaches such as sociolinguistic surveys, analysis of discourse and observational methods of data collection. Results show that although symbols of religion and culture are retained, code switching in Arab-English greetings is growing among the younger generations, especially in the work environment. Gender is important as it shapes the style of greeting in the workplace, and male interactions with male colleagues showed more physical intimacy than across-gender interactions. The study adds to the knowledge of Arabic sociolinguistics, intercultural communication in Middle Eastern contexts and the maintenance and safeguard of cultural identity in the age of globalization.
Keywords: Iraqi Arabic; Greeting Practices; Sociolinguistics; Workplace Etiquette; Politeness Theory; Code-Switching